Serum per‐ and polyfluoroalkyl substance concentrations in four municipal US fire departments. Issue 5 (21st July 2022) - Burgess, Jefferey L.; Fisher, Julia M.; Nematollahi, Amy; Jung, Alesia M.; Calkins, Miriam M.; Graber, Judith M.; Grant, Casey C.; Beitel, Shawn C.; Littau, Sally R.; Gulotta, John J.; Wallentine, Darin D.; Hughes, R. Jeffrey; et al.
Abstract: Background: Firefighters have occupational and environmental exposures to per‐ and polyfluoroalkyl substances (PFAS). The goal of this study was to compare serum PFAS concentrations across multiple United States fire departments to National Health and Nutrition Examination Survey (NHANES) participants. Methods: Nine serum PFAS were compared in 290 firefighters from four municipal fire departments (coded A–D) and three NHANES participants matched to each firefighter on sex, ethnicity, age, and PFAS collection year. Only Departments A and C had sufficient women study participants (25 and six, respectively) to compare with NHANES. Results: In male firefighters compared with NHANES, geometric mean perfluorohexane sulfonate (PFHxS) was elevated in Departments A–C, sum of branched perfluoromethylheptane sulfonate isomers (Sm‐PFOS) was elevated in all four departments, linear perfluorooctane sulfonate (n‐PFOS) was elevated in Departments B and C, linear perfluorooctanoate (n‐PFOA) was elevated in Departments B–D, and perfluorononanoate (PFNA) was elevated in Departments B–D, but lower in A. In male firefighters compared with NHANES, perfluoroundecanoate (PFUnDA) was more frequently detected in Departments B and D, and 2‐( N ‐methyl‐perfluorooctane sulfonamido) acetate (MeFOSAA) was less frequently detected in Departments B–D. In female firefighters compared with NHANES, PFHxS and Sm‐PFOS concentrations were elevated in Departments A and C. Other PFAS concentrations were elevated and/or reduced in only one department or not significantly different from NHANES in any department. Conclusions: Serum PFHxS, Sm‐PFOS, n‐PFOS, n‐PFOA, and PFNA concentrations were increased in at least two of four fire departments in comparison to NHANES.